Synthesis, Characterization, and Elimination of Amoxicillin by Using V2O5 and NiO Nanoparticles - Jehad, Ali. M.; Rasheed, Rashed T. (Iraqi Journal of Science, 2026)
The nanoparticles (V2O5 and NiO) were synthesized via reflux and characterized using various techniques including atomic force microscopy (AFM), scanning electron microscopy (SEM), X-ray diffraction (XRD), UV/visible spectroscopy, and Fourier-transform infrared spectroscopy (FTIR). Initially, the nanoparticles were dried at 90 oC, to obtain the as prepared nanoparticles (V2O5.1.8H2O and Ni(OH)2), followed by annealing at 500 oC to produce the oxide nanoparticles (V2O5 and NiO). The average grain sizes of the nanoparticles as prepared were 30.51nm, 55.70 nm, which decreased to 21.49 nm and 37.07 nm after annealing, respectively. The nanoparticles were employed for the removal of amoxicillin (AMX) as a contaminant in a water solution. V2O5.1.8H2O nanoparticles exhibited the most effective removal activity among all types of nanoparticles, with a percentage removal (%R) of 64.01% and a removal capacity (qt) of 5.89 g/mg. Therefore, vanadium pentoxide in its prepared form (V2O5.1.8H2O) demonstrated the best removal activity.